Contrastive Analysis between English and Indonesian Consonants and Its Reflection toward Students’ Errors in Reading Aloud at Eighth Level Students of SMP Negeri 12 Palembang - Rini Anggraini (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACT Everyone acquires sounds as the first component in learning English and his native. Linguistically those systems have some similarities and differences. This study dealt with Contrastive Analysis between English and Indonesian Consonants and Its Reflection toward Students’ Errors in  Reading Aloud at Eight Level  Students of SMP Negeri 12 Palembang. The writer used descriptive method and the data were analyzed qualitatively. The result of study showed that some differences between English and Indonesian consonants caused some difficulties for students in producing English consonants such as; the substitutions for English /θ, ð, ζ/, the transformation of English palatal into Indonesian palatal, lack of aspiration with English voiceless stops [p,t,k] and neglecting the sound /g/ or /k/ after uttering the sound /ŋ/. This prediction reflects some errors made by students in pronouncing English /θ,ð,f,v, ŋ/, English /tʅ and dζ/, English /p,t,k/, neglecting the consonant clusters in final position, and neutralizing English voiced consonant in final position.  Key Words:  Contrastive analysis, Errors Analysis and English and Indonesian Consonants